Pengujian Efisiensi Dan Peningkatan Efisiensi Bentuk Lemah Bursa Efek Indonesia Pada Saat Dan Sesudah Krisis Moneter Pada Saham-Saham LQ-45 - Ibnu Khajar (Jurnal Manajemen Teori dan Terapan, 2008)
Efficient markets can be classified into three forms: weak, semi-strong, and strong. Weak-form efficiency suggests that security prices reflect all trade-related information, such as historical security price movements and volume of securities trades, so they don’t relate with current price and volume. In other words, historical price movements independent or random over time. Thus, test of weak-form efficiency is ralated with random walk theory. This research has two objectives. The first objective is to analyze whether Indonesian capital market has been efficient (weak-form). The second one is to analyze increasing efficient market in two different periode. The study was carried out on the 10 stock in the LQ-45 index, based on crisis and after crisis during 1998 and 2006 period. The first objective was analyzed by using run and autocorrelation test. The result shows that most stock are random in two different period. The second one was analyzed by searching number stocks that is random in crisis and after crisis period. The result shows there is not increasing weak-form efficiency